STAT!ref platform. Issue 2 (3rd April 2018) - Weeks, Aidy
Abstract: STAT!Ref is a versatile e-resources platform that offers customized collections and standard features not seen in similar e-book vendor collections. The platform sets itself apart with its proprietary, full-text, cross-search capabilities that allow users to conduct keyword searches from a multitude of e-mediums, such as e-books, media collections, clinical reference tools, and nonsubscribed sources such as PubMed. As a third-party vendor, STAT!Ref offers a range of e-resources from more than 40 publishers as well as subscription options from Product Partnership content hosted within the platform. STAT!Ref is available for the desktop and comes with STAT!Ref Mobile App Access for Android and Apple devices.